Pembelajaran Seni Rupa Dengan Driil Method (Metode Latihan Keterampilan ) Disertai Demostrasi Pada Materi Karya 2 Dimensi (Karya Seni Madala) Siswa Kelas X TJKT SMK Negeri 1 Pangkep.: . - Damayanti, Reski; Zariya, Ainun; Syahri, Andi Alim (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Classroom Action Research (PTK) which was conducted at UPTD SMKN 1 Pangkep which began on August 19, 2022 with class X subjects starting with initial observation activities of the learning process in class. The activities carried out during the observation were observing the extent to which class X students' abilities in Fine Arts lessons, observing the learning process which included the methods and media used and observing students' attitudes during the lesson. The purpose of this class action research was to improve the quality of fine arts learning for class X students of SMKN 1 Pangkep through the Drill Method and Demonstration learning.